Optimising White Wheat Bread Fortification with Vitamin D3 and Dietary Fibre: Balancing Nutritional Enhancement and Technological Quality - Sabrina Boudrag; Elke K. Arendt; Celia Segura Godoy; Aylin W. Sahin; Laura Nyhan; Kevin D. Cashman; Emanuele Zannini (Foods)
Inadequate vitamin D and dietary fibre intake are growing public health concerns in Western countries, especially in regions with limited sunlight and diets rich in processed foods. Bakery products, widely consumed, offer a promising opportunity for nutritional fortification. This study explored the possibility of fortifying white wheat bread—a staple food but low in fibre—with vitamin D3 and various dietary fibres (oat fibre, pectin, cellulose, and beta-glucan). The goal was to enhance its nutritional profile while maintaining desirable bread qualities. Using Response Surface Methodology (RSM), an empirical model, optimised the fibre combination. A range of dough and bread analyses were conducted—including assessments of gluten structure, starch pasting, fermentation activity, crumb hardness, specific volume, and colourimetry. The results showed fibre addition weakened the gluten network and altered starch properties (reduced peak, final and breakdown viscosities)—reducing loaf volume (4.2 ± 0.4 mL/g vs. 4.8 ± 0.1 mL/g for the control)—though to a lesser extent than in wholemeal bread (2.4 ± 0.1 mL/g), while vitamin D3 inclusion had a minimal impact (4.0 ± 0.4 mL/g for white bread, 2.1 ± 0.0 mL/g for wholemeal bread). The study identified an optimal mix of soluble and insoluble fibres with vitamin D3 that preserved the texture, crumb structure, and appearance of standard white bread. The final product offered fibre levels (Total Dietary Fibre, TDF = 10.72 ± 0.31 g/100 g bread, vs. 3.81 ± 0.06 g/100 g for the control) comparable to those of wholemeal bread (TDF = 9.54 ± 0.67 g/100 g), with improved texture and volume. This approach presents an effective strategy to enhance staple foods, potentially improving public health through better nutrient intake without compromising consumer acceptance.